Peradilan Satu Atap ( The One Roof System) Di Indonesia Dan Pengaruhnya Terhadap Peradilan Agama - Malik Ibrahim (Asy-Syir'ah: Jurnal Ilmu Syari'ah dan Hukum, 2013)
The process to one-roof the Religious Court system is not as smooth as the one-roof process of other court institutions. It is full of obstacles and faces pros and cons. Nevertheless, in the early 2004, Religious Court had been made beneath Supreme Court as the executor of the highest judicial power. Therefore, Religious Court as the executor has been authentically experiencing escalating reformation, moreover when the of Law No. 3 of 2006 concerning the Amendment of Law No. 7 of 1989 concerning Religious Court was isseud. This paper is tryingto explain some factors that influence the one-roof process of Indonesian Courts especially Religious Court as well as the effects of one-roof court implementation towards the existence of ReligiousCourt in Indonesia.